2014
DOI: 10.7315/jcde.2014.021
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the virtual commissioning of manufacturing systems

Abstract: This paper reviews and identifies issues in the application of virtual commissioning technology for automated manufacturing systems. While the real commissioning of a manufacturing system involves a real plant system and a real controller, the virtual commissioning deals with a virtual plant model and a real controller. The expected benefits of virtual commissioning are the reduction of debugging and correction efforts during the subsequent real commissioning stage. However, it requires a virtual plant model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(86 citation statements)
references
References 44 publications
1
81
0
4
Order By: Relevance
“…LITERATURA w ramach etapu VE przeprowadzana jest weryfikacja oprogramowania systemu sterującego zgodnie z podejściem HiL (Hardware in the Loop). VC umożliwia wstęp-ną ocenę, optymalizację i walidację całego systemu produkcyjnego, a zwłaszcza integrację wszystkich zasobów: produktu, procesu, mechanicznych i elektrycznych komponentów oraz oprogramowania [10].…”
Section: Podsumowanieunclassified
“…LITERATURA w ramach etapu VE przeprowadzana jest weryfikacja oprogramowania systemu sterującego zgodnie z podejściem HiL (Hardware in the Loop). VC umożliwia wstęp-ną ocenę, optymalizację i walidację całego systemu produkcyjnego, a zwłaszcza integrację wszystkich zasobów: produktu, procesu, mechanicznych i elektrycznych komponentów oraz oprogramowania [10].…”
Section: Podsumowanieunclassified
“…The tools also allow simulated devices to be controlled by a real control system. This setup is commonly referred to as virtual commissioning (VC) (Lee and Park, 2014).…”
Section: Virtual Manufacturing and Commissioningmentioning
confidence: 99%
“…The main motivation to use VC is to reduce testing and integration time during development (Hoffmann et al, 2010;Park and Chang, 2012;Lee and Park, 2014). This is achieved by being able to test and integrate the control system before the physical production system is completely installed.…”
Section: Virtual Manufacturing and Commissioningmentioning
confidence: 99%
“…Thus, operations of the continuous detection systems have to be reprocessed for applying to the discrete-event simulation system. Previous research and existing tools for simulation system frameworks have been reported for various fields, such as engineering design [7], manufacturing simulation [8][9][10], and traffic control simulation. But these frameworks are for simulations which require only discreteevents, rather than including continuous-state systems.…”
Section: Introductionmentioning
confidence: 99%